Simple one pot synthesis of nano gold-mesoporous silica and its oxidation catalysis - Sekhar, A. C. Sunil; Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S.; Vinod, C. P. (Catalysis Today, 2012)
A simple one pot synthesis strategy using a non ionic triblock copolymer P123 as reducing as well as templating agent has been employed to prepare nano gold particles incorporated in the pores of mesoporous silica catalyst. The catalyst is characterized by XRD, nitrogen adsorption desorption isotherms at 77 K and TEM. The presence of small gold nanopartilces (similar to 2-4 nm) clearly demonstrated that this strategy can be effective in incorporating Au inside mesochannels. The catalyst reduced at 300 degrees C in H-2 was found to be active for oxidation reactions, such as CO oxidation, and benzyl alcohol. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Alcohol oxidation; CO oxidation; Gold catalysis; Mesoporous silica

Synthesis and catalytic activity of monodisperse gold-mesoporous silica core-shell nanocatalysts - Sekhar, A. C. Sunil; Meera, C. J.; Kottavarithottil Ziyad; Gopinath, Chinnakonda S.; Vinod, C. P. (Catalysis Science & Technology, 2013)
Core-shell nanostructures, where gold nanoparticles of sub 10 nm size are successfully encapsulated inside porous silica spheres, have been prepared. The detailed characterization of the catalyst shows a high surface area and good mesoporosity. The sinter resistance of the catalyst under repeated cycles of the CO oxidation reaction is observed.

Structure sensitive chemical reactivity by palladium concave nanocubes and nanoflowers synthesised by a seed mediated procedure in aqueous medium - Sreedhal, S.; Sudheeshkumar, V.; Vinod, C. P. (Nanoscale, 2014)
Palladium nanocubes and their transformation to concave nanocubes and nanoflowers are realised by a seed mediated procedure in aqueous medium and at room temperature using cationic surfactants. The concave nanocubes and nanoflowers were found to be enclosed by high index facets. The under coordinated atoms present on the high index facets make these nanostructures chemically more active towards Suzuki coupling and Heck coupling reactions compared to the conventional nanocubes and spherical nanoparticles of similar size.

Surfactant assisted formation of ruthenium nanochains under mild conditions and their catalytic CO oxidation activity - Sreedhala, S.; Vinod, C. P. (Chemical Communications, 2015)
Spontaneous formation of ruthenium nanochains is accomplished in aqueous medium under mild conditions using a seed mediated protocol with cetyl trimethylammonium bromide (CTAB) as the capping agent. They are formed due to the random self-assembly of Ru seeds of similar to 3.5 nm size. These 1D nanostructures exhibit better catalytic activity towards the oxidation of CO relative to the similar to 3.5 nmseeds and 6 nm Ru nanospheres. The synthesis strategy adopted here is found to be simple, facile and environmentally friendly.

Surfactant free synthesis of Au@Ni core-shell nanochains in aqueous medium as efficient transfer hydrogenation catalyst - Vysakh, A. B.; Shebin, K. J.; Jain, Ruchi; Sumanta, P.; Gopinath, Chinnakonda S.; Vinod, C. P. (Applied Catalysis A-General, 2019)
A surfactant free aqueous phase synthesis method is reported for the generation of highly lattice mismatched Au@Ni core-shell nanochains without using any expensive and hazardous organic ligands. As synthesised Au@Ni nanochain structures showed high thermal stability and bulk oxidation resistance up to 300 degrees C. In situ near ambient pressure XPS (NAPXPS) analysis has been done for the bare Au@Ni nanochain surfaces under oxygen atmosphere and at different temperatures which showed evidence for the surface oxidation resistance of naked Au@Ni nanochains up to 200 degrees C. Ligand or capping agent free Au@Ni nanochain surfaces are found to be highly active for transfer hydrogenation of acetophenone to 1-phenyl ethanol an important commodity in perfumery industry.
Keywords: Au@Ni nanochains; core-shell; NAPXPS; Surfactant free; synergistic effects; transfer hydrogenation

Spectroscopic evidences for the size dependent generation of pd species responsible for the low temperature CO oxidation activity on Pd-SBA-15 nanocatalyst - Soni, Yogita; Pradhan, Sumanta; Bamnia, Mahesh K.; Yadav, A. K.; Jha, S. N.; Bhattacharyya, D.; Khan, Tuhin Suvra; Haider, M. A.; Vinod, C. P. (Applied Catalysis B-Environmental, 2020)
A comprehensive size dependent CO oxidation activity has been demonstrated for Pd-SBA-15 catalysts with Pd NPs of varying sizes such as 1-2, 4-6 and 7-10 nm. Pd-SBA-15 catalyst with smallest sized NPs (Pd-S-N) has been synthesized by modified deposition precipitation method recently developed in our lab. Pd-S-N catalyst (reduced at 400 degrees C) demonstrated CO oxidation activity with lower light off temperature (50 degrees C), clearly one of the best reported for a Pd-silica system. A detailed XPS and in-situ DRIFTS analyses further supported by XAS and DFT calculations reveal the presence of easily decomposable highvalent Pd-oxide on co-ordinatively unsaturated Pd sites (Pdcus). Weak binding of CO on Pdcus sites in small Pd NPs leaving sites for oxygen activation is attributed to the low temperature activity of Pd-S-N for CO oxidation.
Keywords: CO oxidation; high-valent Pd species; Pd nanoparticles; SBA-15; under coordinated Pd atoms

Stress-induced electronic structure modulation of manganese-incorporated Ni2P leading to enhanced activity for water splitting - Sarkar, Shreya; Dheer, Lakshay; Vinod, C. P.; Thapa, Ranjit; Waghmare, V. Umesh; Peter, Sebastian C. (ACS Applied Energy Materials, 2020)
The cornerstone of the emerging hydrogen economy is hydrogen production by water electrolysis with concomitant oxygen generation. Incorporating a third element in metal phosphides can tune the crystalline and electronic structure, hence improving the electrocatalytic properties. In this work, Mn-doped Ni2P with varying ratios of Mn and Ni has been explored as excellent catalysts for water splitting. A complete cell made of the best catalyst Ni1.5Mn0.5P electrodes showed low voltage of 1.75 V at a current density of 10 mA cm(-2) due to enhanced electrical conductivity, induction of tensile stress, enhanced electrochemical surface area, and increased electric dipole upon Mn incorporation.
Keywords: Electronic Structure; hydrogen evolution reaction; Oxygen Evolution Reaction; phosphides; water splitting

Structure-tailored non-noble metal-based ternary chalcogenide nanocrystals for pt-like electrocatalytic hydrogen production - Sarkar, Shreya; Rawat, Abhishek; Das, Tisita; Gaboardi, Mattia; Chakraborty, Sudip; Vinod, C. P.; Peter, Sebastian C. (ChemSusChem, 2021)
A facile microwave-assisted strategy was employed to synthesize Ni3Bi2S2 nanocrystals. Variation in the synthesis conditions tuned the composition of monoclinic and orthorhombic phases of Ni3Bi2S2. The electrochemical hydrogen evolution activity of the catalyst with highest percentage of monoclinic phase demonstrated a negligible onset potential of only 24 mV close to that of state-of-the-art Pt/C with an overpotential as low as 88 mV. Density functional theory calculations predicted the monoclinic phase exhibit the lowest adsorption free energy corresponding to hydrogen adsorption (Delta GadsH*) and, therefore, the highest hydrogen evolution activity amongst the considered phases. The quasi-2D structure of monoclinic phase facilitated an increased charge-transfer between Ni and Bi, favoring the downward shift of the d-band center to enhance the catalytic activity.
Keywords: charge transfer; electrocatalysis; hydrogen evolution reaction; Nanomaterials; ternary chalcogenides

`Self-activating' Bi3TaO7-Bi4TaO8Br photocatalyst and its use in the sustainable production of pro-fluorophoric rhodamine-110 - Banoo, Maqsuma; Chatterjee, Kaustav; Mondal, Sanjit; Vinod, C. P.; Gautam, Ujjal K. (Green Chemistry, 2022)
We counter two common notions that (i) photocatalysts are likely to degrade during use with barely any strategy to counter it and (ii) rhodamine-B (RhB) photo-degradation lacks any useful or commercial prospects even after 53 years of its discovery by developing a photocatalyst that continues to improve its activity for similar to 300 h due to a leaching induced `self-activation' process. Rhodamine-110 (Rh110) is a widely used pro-fluorophore in biological studies. However, its commercial production is highly challenging due to the formation of various side-products originating from the presence of the two labile amino side-groups that induce the pro-fluorophore activity, leading to purification difficulties, low yield, and unusually high costs. Herein, we demonstrate a facile strategy to produce pure Rh110 using extremely inexpensive RhB and Bi3TaO7-Bi4TaO8Br heterostructures as a catalyst in sunlight. The catalyst is not just stable over 30 catalytic cycles but also gets activated continuously in successive cycles to produce a reaction yield as high as 88%. The role of the heterostructure, the origin of surface activation, and the RhB -> Rh110 transformation mechanism have been established. Based on 150 days of sunlight experiments, large-scale production prospects (similar to 4000 times scale-up) and isolation of Rh110 have also been realized, paving a novel way for its production by anyone, inexpensive biological essaying, and device fabrication. Continuously improving catalysts are unknown and compensatory leaching of metal atoms from the catalyst surface may pave the way to realize them.

Single-step insertion of M-Nx moieties in commercial carbon for sustainable bifunctional electrocatalysis: mapping insertion capacity, mass loss, and carbon reconstruction - Garg, Reeya; Sahoo, Lipipuspa; Kaur, Komalpreet; Vinod, C. P.; Gautam, Ujjal K. (Carbon, 2022)
Atomically dispersed earth-abundant metals in N-doped carbon (M-N-Cs) have emerged as a new class of electroactive materials that can match not only the performance of the precious metals but can catalyze both the cathodic and the anodic reactions due to their bifunctional behaviour. This inspires the development of simpler strategies for scale-up production since the existing ones rely on precursors whose commercial viability is not yet ascertained. Herein, we demonstrate the insertion prospects of M-Nx (M = Fe, Co, Ni) moieties, the electrocatalytic centers in the M-N-Cs, into commercial carbon to establish that a single-step heating of the inexpensive precursors is sufficient to generate bifunctional electrocatalysts for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) with efficiencies that bypass the majority of the known catalysts. Further importantly, we quantify both the ORR and OER trends and the metal insertion limits for each metal while maintaining an atomic dispersion, without the formation of surface migration-induced clustering, because such clustering is inevitable in the existing processes to necessitate an extra acid-leaching step to remove them. We further quantify and explain for each metal a negative mass balance originating from anomalous mass loss of both metal and carbon content, and a massive reconstruction of the carbon backbone catalyzed by the very metal, an event documented for the first time though it ought to be associated with other M-N-C syntheses too. The study establishes an incredibly simple and inexpensive strategy for the realization of M-N-Cs and outlines the parameters to be considered during mass-production.
Keywords: Bifunctional catalysis; Carbon reconstruction; Commercial carbon; Metal insertion; Oxygen electrocatalysis

Strain-enhanced phase transformation of iron oxide for higher alcohol production from CO2 - Goud, Devender; Churipard, Sathyapal R.; Bagchi, Debabrata; Singh, Ashutosh Kumar; Riyaz, Mohd; Vinod, C. P.; Peter, Sebastian C. (ACS Catalysis, 2022)
Conversion of CO2 to higher alcohols (HAs) and higher hydrocarbons (HCs) has a greater advantage compared to C1 products because of their high energy density and wide range of applications in daily life. Despite the immense potential of these chemicals, not much of scientific research has been focused on the conversion of CO2 to HAs. In the present work, we have introduced the concept of strain in designing the material to enhance the CO(2 )to HA performance. We introduced strain in a traditional iron-based catalyst, Fe2O3, by the introduction of indium (In), which facilitates the selective conversion of CO2 to HA. An optimum strain favored a 36.7% CO2 conversion with a 42% HA selectivity, and a record yield of 15.42%. The strain has been tuned further with the introduction of K as a promoter. The introduced strain upon In substitution and K promotion favored the conversion of CO2, which is mapped by powder X-ray diffraction, X-ray photoelectron spectroscopy, and X-ray absorption spectroscopy. Further, the change in the mechanism upon In incorporation and K promotion has been probed by in situ diffuse reflectance infrared fourier transform spectroscopy, and it is found that the OCHx intermediate, which produces HAs, is more prominent upon In substitution, which favored the enhancement of HA production compared to that of pristine Fe2O3.
Keywords: CO2 to HA; Fischer-Tropsch synthesis (FTS); Phase transformation; reverse water gas shift (RWGS) reaction; strain

Structure-tailored surface oxide on Cu-Ga intermetallics enhances CO2 reduction selectivity to methanol at ultralow potential - Bagchi, Debabrata; Raj, Jithu; Singh, Ashutosh Kumar; Cherevotan, Arjun; Roy, Soumyabrata; Manoj, Kaja Sai; Vinod, C. P.; Peter, Sebastian C. (Advanced Materials, 2022)
Electrochemical CO2 reduction reaction (eCO(2)RR) is performed on two intermetallic compounds formed by copper and gallium metals (CuGa2 and Cu9Ga4). Among them, CuGa2 selectively converts CO2 to methanol with remarkable Faradaic efficiency of 77.26% at an extremely low potential of -0.3 V vs RHE. The high performance of CuGa2 compared to Cu9Ga4 is driven by its unique 2D structure, which retains surface and subsurface oxide species (Ga2O3) even in the reduction atmosphere. The Ga2O3 species is mapped by X-ray photoelectron spectroscopy (XPS) and X-ray absorption fine structure (XAFS) techniques and electrochemical measurements. The eCO(2)RR selectivity to methanol are decreased at higher potential due to the lattice expansion caused by the reduction of the Ga2O3, which is probed by in situ XAFS, quasi in situ powder X-ray diffraction, and ex situ XPS measurements. The mechanism of the formation of methanol is visualized by in situ infrared (IR) spectroscopy and the source of the carbon of methanol at the molecular level is confirmed from the isotope-labeling experiments in presence of (CO2)-C-13. Finally, to minimize the mass transport limitations and improve the overall eCO(2)RR performance, a poly(tetrafluoroethylene)-based gas diffusion electrode is used in the flow cell configuration.
Keywords: (2) reduction; CO; Electrochemistry; Methanol

Selective hydrogenation of furfural to furfuryl alcohol over Pd supported on ternary oxide in aqueous medium under mild conditions - Nehra, Pooja; Betsy, K. J.; Vinod, C. P. (ChemCatChem, 2025)
We report palladium (Pd) supported on a mixed CuO/ZnO/Al2O3 catalyst for the synthesis of furfuryl alcohol (FA) from furfural (FF) using hydrogen under near atmospheric pressure (balloon pressure) conditions. A systematic study of various metal oxide combinations revealed that the best support for Pd nanoparticles is a CuO/ZnO/Al2O3 mixed system, which results in excellent catalytic performance. A series of control experiments highlighted the essential role of mixed Cu-Zn-Al oxide support in facilitating the adsorption and activation of FF. Our results demonstrate that under optimal conditions (40 degrees C, balloon pressure H2), the catalyst yields FF conversion exceeding 98%, with remarkable selectivity for FA reaching up to 99% with water as solvent. The catalyst exhibited almost comparable activity up to three catalytic cycles without extra catalyst treatment or reactivation with negligible Pd leaching. These findings shed insight into the design of mixed metal oxide-based support for active metal interactions in optimizing catalytic performance in furfural hydrogenation under mild conditions.
Keywords: Biomass conversion; Furfural hydrogenation; Furfuryl alcohol; mixed metal oxides; Pd catalyst